Transcriptomics and metabolomics changes triggered by exogenous 6-benzylaminopurine in relieving epicotyl dormancy of Polygonatum cyrtonema Hua seeds - Zhang, Wenwu; Xia, Long; Peng, Fulei; Song, Chenyu; Manzoor, Muhammad Aamir; Cai, Yongping; Jin, Qing (Frontiers in Plant Science, 2022)
Polygonatum cyrtonema Hua is one of the most useful herbs in traditional Chinese medicine and widely used in medicinal and edible perennial plant. However,the seeds have the characteristics of epicotyl dormancy. In this study, the molecular basis for relieving epicotyl dormancy of P. cyrtonema seeds under exogenous 6 - BA treatment was revealed for the first time through transcriptome and metabolomics analysis. We determined the elongation of epicotyl buds as a critical period for dormancy release and found that the content of trans-zeatin, proline, auxin and gibberellin was higher, while flavonoids and arginine were lower in the treatment group. Transcriptome analysis showed that there were significant differences in gene expression in related pathways, and the expression patterns were highly consistent with the change of metabolites in corresponding pathways. Co-expression analysis showed that cytokinin dehydrogenase of P. cyrtonema (PcCKXs) and pelargonidin in flavonoid biosynthesis, as well as L-proline, L-ornithine, and L-Citrulline in arginine and proline metabolism form network modules, indicating that they have related regulatory roles. Above all, our findings provide new insight into the exogenous 6 - BA relieving epicotyl dormancy of P. cyrtonema seeds.